2013
DOI: 10.1016/j.ijpddr.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative tissue pharmacokinetics and efficacy of moxidectin, abamectin and ivermectin in lambs infected with resistant nematodes: Impact of drug treatments on parasite P-glycoprotein expression

Abstract: Graphical abstractHighlights► Macrocyclic lactones share some structural and physico-chemical properties. ► The kinetic-dynamic differences of these compounds should be addressed under in vivo standardized conditions. ► Lower concentrations of moxidectin were obtained in resistant Haemonchus contortus. ► Moxidectin showed a higher efficacy against resistant H. contortus. ► The P-glycoprotein expression in H. contortus was increased after ivermectin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
71
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 42 publications
6
71
1
Order By: Relevance
“…These results are in full agreement with data from previous in vivo studies, which showed that MOX efficacy is maintained at higher levels than is IVM efficacy as ML resistance develops, as well as in vitro studies on drug-resistant parasitic nematodes, where MOX was more potent than IVM, while EPR was the least potent drug, displaying the highest resistance ratio compared to IVM and MOX (35,(43)(44)(45)(46)(47)(48)(49)(50)(51). These similarities with the ML-selected C. elegans strains clearly show that the model of drug selection pressure in C. elegans can be relevant to studies of the adaptation of parasitic nematodes to ML treatment in the field.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are in full agreement with data from previous in vivo studies, which showed that MOX efficacy is maintained at higher levels than is IVM efficacy as ML resistance develops, as well as in vitro studies on drug-resistant parasitic nematodes, where MOX was more potent than IVM, while EPR was the least potent drug, displaying the highest resistance ratio compared to IVM and MOX (35,(43)(44)(45)(46)(47)(48)(49)(50)(51). These similarities with the ML-selected C. elegans strains clearly show that the model of drug selection pressure in C. elegans can be relevant to studies of the adaptation of parasitic nematodes to ML treatment in the field.…”
Section: Discussionsupporting
confidence: 91%
“…Since PGP6 is expressed in the amphids, its overexpression could help protect the nematodes from the effects of ML on extrapharyngeal neurons associated with the amphids. In addition, our results show the constitutive overexpression of Pgp2, Pgp9, and Pgp11 after both IVM and MOX selection, in accordance with the association of their homologs in ML resistance in H. contortus, Teladorsagia circumcincta, and Parascaris equorum (13,43,44,58,59). Generally, a similar pattern of expression of the regulated genes was found in the IVM-selected and the MOX-selected strains, in agreement with the similar transcriptional profiles of the multidrug resistance-associated proteins (MRPs) in C. elegans (8) and ABC transporters in C. oncophora (10) following exposure to IVM and MOX.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As can be seen in Table 2, this anthelmintic showed the highest effectiveness rate (stand-alone) in five studies involving sheep (CUNHA et al, 1998;THOMAZ-SOCCOL et al, 2004;CEZAR et al, 2010;LIMA et al, 2010b;SCZESNY-MORAES et al, 2010) and in three studies involving goats (AHID et al, 2007; RODRIGUES et al, 2007; LIMA et al, 2010b). Although its mechanism of action is similar to that of ivermectin, several authors around the world have observed the greater effectiveness of moxidectin in strains resistant to ivermectin (BARNES et al, 2001;VICKERS et al, 2001;LLOBERAS et al, 2013). Prichard et al (2012) ascribed the difference in the effectiveness of these two antiparasitics to different interactions in glutamate-gated ion channels where they act, and to different levels of expression of ABC proteins.…”
Section: Developments In Research and The Effectiveness Of Anthelmintmentioning
confidence: 95%
“…Prichard et al (2012) ascribed the difference in the effectiveness of these two antiparasitics to different interactions in glutamate-gated ion channels where they act, and to different levels of expression of ABC proteins. However, these proteins can cause cross-resistance between the two anthelmintics, owing to an overexpression of P-glycoprotein in response to the ordinary use of ivermectin, which may interfere in the effectiveness of moxidectin (LLOBERAS et al, 2013). This may explain the low effectiveness of moxidectin found in recent studies in Brazil (BUZZULINI et al, 2007;ROSALINSKI-MORAES et al, 2007;VERÍSSIMO et al, 2012;OLIVEIRA et al, 2014), where ivermectin is widely used.…”
Section: Developments In Research and The Effectiveness Of Anthelmintmentioning
confidence: 99%